Review on Workflow Scheduling In Cloud Environment: A Comprehensive Study (International Journal of Innovative Research in Computer Science & Technology, 2021)
For enterprise application development,  cloud computing is going to new-fangled paradigm that  meets the needs of today's enterprises and helps them  efficiently executing workflows in business and scientific  applications. Workflow applications often require a very  intricate runtime environment that is hard to create and  maintain. Thus, cloud infrastructure is valued as an  implementation platform for positioning technical  workflows with features such as on-demand provisioning,  scalability, reproducibility and resilience. To schedule  multiple workflows in the cloud, we need to design the  workflow before scheduling it. Therefore, in this paper we  review the diverse work done by researchers for the  workflow design as well as workflow scheduling.
Keywords: Cloud Computing; Distributed Computing; Work Flow Scheduling; Benefit Of Clouds; Load Balancing